Moisture Modes of Tropical Intraseasonal Oscillations—High Order and Anti‐Symmetric Solutions. Issue 14 (19th July 2022) - Wang, Shuguang; Tan, Zhe‐Min; Wu, Zhaohua; Fang, Juan
Abstract: The Madden Julian Oscillation (MJO) and the Boreal Summer Intraseasonal Oscillation are fundamental climate modes in the tropical atmosphere on the intraseasonal time scales. A recent study developed a linear moisture mode theory for unified treatment of these intraseasonal oscillations under different meridional moisture gradients. Using scaled Hermite polynomials as the basis for the meridional structure, it is shown that the system has infinite number of normal modes under the same parameter values, as n → ∞ . The v = 0 and n = 1 analyzed in the previous study are two special cases. These moisture modes are non‐orthogonal. The idealized MJO solutions derived using the parameters in the boreal winter conditions bear similar meridional structure for planetary scale waves in the Earth‐like atmosphere, unlike the higher order solutions (which are often considered unrealistic) in the classical tropical waves theory. The solutions include both symmetric and anti‐symmetric modes. The symmetric modes are analogous to the Kelvin‐Rossby wave paradigm of the MJO. The anti‐symmetric modes features cross‐equatorial flow near the equator and subtropical gyres. Both growth rates and frequencies of the scaled higher order n modes display small increments compared to lower order modes. In the asymptotic limit n → ∞, a growth rate higher than other modes with finite n is achieved. Plain Language Summary: The Madden Julian Oscillation and the Boreal Summer Intraseasonal Oscillation are important waves in the tropical atmosphere. These large‐scale waves are traditionally difficult to understand because of the lack of the mathematical theory. Here we develop a new theory to understand these tropical waves. We show that the wave solution is not unique; but there exist infinite number of solutions which are very similar to each other in the spatial pattern and period. Key Points: Higher order moisture mode solutions are derived based on scaled Hermite polynomials The anti‐symmetric solutions are characterized by cross‐equatorial winds near the equator and subtropical gyres Both the growth rate and the meridional structure converge at the asymptotic limit n → ∞